Product Development of Diffusion Solution from Citrus reticulata Blanco Essential Oil - Tran Thien Hien; Nguyen Nam Do; Mai Huynh Cang (Science and Technology Indonesia, 2026)
The aim of this study was to develop a diffuser solution product from Citrus reticulata Blanco essential oil, which was recovered by hydrodistillation. The hydrodistillation process was influenced by factors such as: raw material grinding time (grinding for 40s); raw material/solvent ratio (1/3 g/mL); raw material moisture content (70%), and extraction time (120 min) with an essential oil content of 0.254 mL/g dw. Using gas chromatography-mass spectrometry (GC-MS), 21 chemical components in Citrus reticulata essential oil were identified, of which the main compound was limonene, accounting for 94.64%. Thanks to its biological activities, Citrus reticulata essential oil is widely used in the field of developing household care products, including diffuser solutions. The results showed that with the IPM base oil content of 25%, the essential oil content of 40%, and the emulsifier PEG-40 of 20% combined with 96% ethanol at a content of 5%, preserved in a dark glass bottle to bring a product with good sensory scores in terms of uniformity, scent, and volatility. The diffuser solution product created helps to utilize the by-product material from Citrus reticulata peel to produce essential oil, contributing to increasing the usage value of the Citrus reticulata tree. This study is novel in that it combines hydrodistillation-process selection with the formulation of a passive diffuser solution from Citrus reticulata peels by-products, thereby connecting essential-oil recovery with aroma-delivery design in a single product-oriented workflow.